Diffuse Cutaneous Bullous Mastocytosis and Disseminated Intravascular Coagulation Postvaccination: A Case Report. Issue 6 (November 2016) - Hudson, Alexandra; Finlayson, Laura
Background: Diffuse cutaneous bullous mastocytosis is the most rare subtype of cutaneous mastocytosis, characterized by generalized skin infiltration with mast cells and blistering. Objective: To increase the awareness of the natural history and potential adverse complications of this rare cutaneous condition. Method and Results: We report a case of a male diagnosed on day 7 of life with follow-up of his progression over 6 years. When he was 2.5 months old, he was admitted to hospital postvaccinations with a flare of his blistering that was complicated by disseminated intravascular coagulation and polyuric acute tubular necrosis. Blistering ceased at 3 years, but at 6 years, extensive urtication continued in response to known triggers and a suboptimal dose of mast cell membrane stabilizers and histamine-1 and -2 receptor antagonists. Conclusion: This case discusses the progression of this rare condition over 6 years and highlights the importance of reaching optimal pharmacologic blockage of histamine-1 and -2 receptors and stabilization of mast cell membranes in patients persistently experiencing ongoing pruritus, urtication, and flushing symptoms.